ANALISIS KINERJA KOPERASI UNIT DESA DI WILAYAH KABUPATEN BANYUMAS (PERIODE TAHUN BUKU 2001 - 2004) - Haryadi Haryadi; Rahab Rahab (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2006)
There are four variables in measuring the performance of KUD (unit of cooperative in village) based on Development Ladder Assesment (DLA) Method namely : vision,resources, capacity and networking. This research has two main aim. First, to find out the evaluation variable which gives the highest evaluation on the performance of KUD among vision, capacity, resources, and networking variables. Second, to find out the predicate performance of KUD at Banyumas regency during 2001-2004 using DLA method. KUD samples taken in this research are KUD which including “ A “ clasification according to Small Medium Enterprise and Coopertive Office of Banyumas regency. Research results showed that the resources variable get the highest score compared with other variable whereas networking variable get the lowest score and then KUD performance in Banyumas regency 2001-2004 period got green score predicate based on DLA method.